THE IMPORTANCE OF DESIGNING THE CONTENT OF PHYSICS IN DEVELOPING ENGINEERING SKILLS OF STUDENTS IN CONSTRUCTION ENGINEERING PROGRAMS - Jumayeva Ziyoda Arslonova (Bright Mind Publishing, 2025)
This article examines the issues of substantive redesigning physics based on a competency-based approach in the development of engineering abilities in students studying in the field of construction engineering. The necessity of integrating the physics course with engineering activities, the principles of forming the content, the analysis of modules, the strategies used in the educational process, and the criteria for developing students' professional competencies were scientifically investigated.
Keywords: Physics curriculum design, construction engineering education, competency-based approach, engineering skills, virtual laboratories, simulation, problem-based learning, project-based learning, modular education, engineering competencies.